Identification and expression analysis of ATP-binding cassette (ABC) transporters revealed its role in regulating stress response in pear (Pyrus bretchneideri) - Xiaobing Kou; Zhen Zhao; Xinqi Xu; Chang Li; Juyou Wu; Shaoling Zhang (BMC Genomics, 2024)
Abstract Background ATP-binding cassette (ABC) transporter proteins constitute a plant gene superfamily crucial for growth, development, and responses to environmental stresses. Despite their identification in various plants like maize, rice, and Arabidopsis, little is known about the information on ABC transporters in pear. To investigate the functions of ABC transporters in pear development and abiotic stress response, we conducted an extensive analysis of ABC gene family in the pear genome. Results In this study, 177 ABC transporter genes were successfully identified in the pear genome, classified into seven subfamilies: 8 ABCAs, 40 ABCBs, 24 ABCCs, 8 ABCDs, 9 ABCEs, 8 ABCFs, and 80 ABCGs. Ten motifs were common among all ABC transporter proteins, while distinct motif structures were observed for each subfamily. Distribution analysis revealed 85 PbrABC transporter genes across 17 chromosomes, driven primarily by WGD and dispersed duplication. Cis-regulatory element analysis of PbrABC promoters indicated associations with phytohormones and stress responses. Tissue-specific expression profiles demonstrated varied expression levels across tissues, suggesting diverse functions in development. Furthermore, several PbrABC genes responded to abiotic stresses, with 82 genes sensitive to salt stress, including 40 upregulated and 23 downregulated genes. Additionally, 91 genes were responsive to drought stress, with 22 upregulated and 36 downregulated genes. These findings highlight the pivotal role of PbrABC genes in abiotic stress responses. Conclusion This study provides evolutionary insights into PbrABC transporter genes, establishing a foundation for future research on their functions in pear. The identified motifs, distribution patterns, and stress-responsive expressions contribute to understanding the regulatory mechanisms of ABC transporters in pear. The observed tissue-specific expression profiles suggest diverse roles in developmental processes. Notably, the significant responses to salt and drought stress emphasize the importance of PbrABC genes in mediating adaptive responses. Overall, our study advances the understanding of PbrABC transporter genes in pear, opening avenues for further investigations in plant molecular biology and stress physiology.